Long-term immunogenicity and immune memory response to the hepatitis B antigen in the RTS, S/AS01E malaria vaccine in African children: a randomized trial. Issue 6 (2nd June 2020) - Valéa, Innocent; Adjei, Samuel; Usuf, Effua; Traore, Ousmane; Ansong, Daniel; Tinto, Halidou; Owusu Boateng, Harry; Some, Athanase Mwinessobaonfou; Buabeng, Patrick; Vekemans, Johan; Kotey, Amos; Vandoolaeghe, Pascale; et al.
ABSTRACT: RTS, S/AS01E malaria vaccine contains the hepatitis B virus surface antigen and may thus serve as a potential hepatitis B vaccine. To evaluate the impact of RTS, S/AS01E when implemented in the Expanded Program of Immunization, infants 8–12 weeks old were randomized to receive either RTS, S/AS01E or a licensed hepatitis B control vaccine (HepB), both co-administered with various combinations of the following childhood vaccines: diphtheria-tetanus-acellular pertussis- Haemophilus influenzae type b, trivalent oral poliovirus, pneumococcal non-typeable Haemophilus influenzae protein D conjugate and human rotavirus vaccine. Long-term persistence of antibodies against the circumsporozoite (CS) protein and hepatitis B surface antigen (HBsAg) were assessed, together with the immune memory response to the HB antigen following a booster dose of HepB vaccine. Subgroups receiving RTS, S or the HepB control vaccine were pooled into RTS, S groups and HepB groups, respectively. One month post-HepB booster vaccination, 100% of participants in the RTS, S groups and 98.3% in the control groups had anti-HBs antibody concentrations ≥10 mIU/mL with the geometric mean concentrations (GMCs) at 46634.7 mIU/mL (95% CI: 40561.3; 53617.6) and 9258.2 mIU/mL (95% CI: 6925.3; 12377.0), respectively. Forty-eight months post-primary vaccination anti-CS antibody GMCs ranged from 2.3 EU/mL to 2.7 EU/mL in the RTS, S groups compared to 1.1 EU/mL in the control groups. Hepatitis B priming with the RTS, S/AS01E vaccine was effective and resulted in a memory response to HBsAg as shown by the robust booster response following an additional dose of HepB vaccine. RTS, S/AS01E when co-administered with PHiD-CV, HRV and other childhood vaccines, had an acceptable safety profile.